Satisfaction on the university frontline services: From the lens of transacting students and employees - Marivic A. Gorospe; Ma. Angelita S. Rabanal; Arlene D. Talosa (International Journal of Evaluation and Research in Education (IJERE), 2021)
Client satisfaction is an influential predictor of academic life, such as services delivered with suitable standards. Thus, the study focused on determining the level of client satisfaction on the frontline services of Cagayan State University in Aparri, Philippines from the perspective of students and employees. To assess suitability, relevance, and to ensure adequate and reliable information for the evaluation of the study, the researchers adopted the descriptive- evaluative design and ascertained the level of clients’ satisfaction on the frontline services received and experienced on the campus. The study, however, was limited to the assessment of the respondents on their level of contentment only on the frontline services and providers they have encountered. The results indicated a very high level of satisfaction with which heads of offices have gained higher satisfaction ratings than that of their staff. When grouped according to the respondents’ profile, the older students rated higher the frontline services and providers than the younger ones. At the same time, regular employees have a higher level of satisfaction as compared to non-regular. The result of the study manifests students' and employees’ very high contentment with the actual performances of the frontline service providers.